Growth/differentiation factor-15/macrophage inhibitory cytokine-1 is a novel trophic factor for midbrain dopaminergic neurons in vivo - Strelau, Jens; Böttner, Martina; Lingor, Paul; Suter-Crazzolara, Clemens; Galter, Dagmar; Jászai, József; Krieglstein, Kerstin; Unsicker, Klaus (The journal of neuroscience, 2000)
Transforming growth factor-βs (TGF-βs) constitute an expanding family of multifunctional cytokines with prominent roles in development, cell proliferation, differentiation, and repair. We have cloned, expressed, and raised antibodies against a distant member of the TGF-βs, growth/differentiation factor-15 (GDF-15). GDF-15 is identical to macrophage inhibitory cytokine-1 (MIC-1). GDF-15/MIC-1 mRNA and protein are widely distributed in the developing and adult CNS and peripheral nervous systems, including choroid plexus and CSF. GDF-15/MIC-1 is a potent survival promoting and protective factor for cultured and iron-intoxicated dopaminergic (DAergic) neurons cultured from the embryonic rat midbrain floor. The trophic effect of GDF-15/MIC-1 was not accompanied by an increase in cell proliferation and astroglial maturation, suggesting that GDF-15/MIC-1 probably acts directly on neurons. GDF-15/MIC-1 also protects 6-hydroxydopamine (6-OHDA)-lesioned nigrostriatal DAergic neurons in vivo. Unilateral injections of GDF-15/MIC-1 into the medial forebrain bundle just above the substantia nigra (SN) and into the left ventricle (20 μg each) immediately before a 6-OHDA injection (8 μg) prevented 6-OHDA-induced rotational behavior and significantly reduced losses of DAergic neurons in the SN. This protection was evident for at least 1 month. Administration of 5 μg of GDF-15/MIC-1 in the same paradigm also provided significant neuroprotection. GDF-15/MIC-1 also promoted the serotonergic phenotype of cultured raphe neurons but did not support survival of rat motoneurons. Thus, GDF-15/MIC-1 is a novel neurotrophic factor with prominent effects on DAergic and serotonergic neurons. GDF-15/MIC-1 may therefore have a potential for the treatment of Parkinson's disease and disorders of the serotonergic system.